Prototype Thermoelectric Micro Energy By Utilizing The Heat Of A Sate Stove - Sitopu, Enita; Pratama, Legenda Prameswono; Manfaluthy, Mauludi; Jaenul, Ariep; Dionova, Brainvendra Widi; Putri, Arisa Olivia; Al-Humairi, Safaa Najah Sahud; Mohammed, M.N. (Majalah Ilmiah Teknologi Elektro, 2024)
Electrical energy is one of the primary needs that is very important in people's lives. Along with advances in science and technology (IPTEK) and rapid population growth, the need for electrical energy increases every day. However, research on the use of thermoelectric technology to harvest energy from the heat of satay stoves is still limited and has not been widely applied in renewable energy systems. The aim of this research is to design an energy harvester that utilizes waste heat from a satay stove using a thermoelectric module, so that enough power and voltage can be produced to operate a 12-volt 1-ampere DC fan The research results show that the Thermoelectric Generator (TEG) is capable of producing the highest voltage of 10V with a current of 1.06A at the highest temperature difference of 100°C. By using the Buck-Boost Converter module, the voltage can be increased to 12.6V with a current of 1A. Apart from that, this research also found that the greater the temperature difference from the furnace heat source, the greater the voltage produced by the TEG. When charging the battery, it takes 7 hours to charge from the initial voltage of 11.31V to reach 12.60V, and using the battery for 5 hours shows a decrease in voltage from 12.60V to 11.41V. Thus, utilizing the waste heat energy from satay stoves using thermoelectricity is a solution to help with the power needs of traders. And in the future it can be done with different sources to develop research and increase effective output power.